Comparison of the biophysical profile and modified biophysical profile in prediction of the fetal outcome in pregnancy induced hypertension - Shaikh, Amir Babansab; Chidre, Yogiraj Vaijanathrao (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Pregnancy induces hypertension is one of the major causes of fetal morbidity and mortality. Biophysocal profile is one of the tests performed to predict the fetal outcome which though is simple, is time consuming and costly. This study was performed to compare the modified biophysical profile to the biophysical profile. Methods: 200 patients over the gestation period of 34 weeks with pregnancy induced hypertension were divided into Group A consisting of 100 patients who were studied with biophysical profile (BPP) and Group B consisting of 100 patietns who were studied by the modified biophysical profile (MBPP). Results: Mild hypertension was found in 80% of the cases while 20% of the cases had severe hypertension. Most of the patients were primigravida while very few of them were fourth gravidae. 78 patients had a score of BPP 8-10, out of which 7 had fetal distress while 71. Abnormal BPP score (<6) was observed among 22% of the patients in group A. Of these 22 patients, 9 patients had a score of <2 and all of them delivered by LSCS due to chronic fetal distress. Among the MBPP score, IUGR was seen among 4 fetuses who had a low score. Out of the 5 patients who had fetal distress, 2 fetuses were still born. Both BPP and MBPP were comparable to each other in terms of sensitivity, specificity and the predictive negative and positive values. Conclusions: Since BPP requires more expertise than MBPP in terms of processing and time saving, MBPP can be used as a substitute to BPP.